FUNGSI PENGAWASAN PERADILAN TATA USAHA NEGARA TERHADAP PERBUATAN PEMERINTAH PASCA UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Muhamad Rusjana (PRANATA HUKUM, 2019)
The Administrative Court in the Indonesian Law State is one manifestation of the function supervision by the judicial authorities on the actions of the government. The function of supervision or adjudication of the Administrative Court is to examine, decide and resolve Administrative disputes. The Regulations of administrative law Number 30 of 2014 concerning Government Administration has implications for the expansion of the competence the Administrative Court. The presence of this expansion certainly leads a changes, one of them is the function supervision of the Administrative Court. Based on this research, there is an expansion in the supervisory function of the Administrative Courts including: 1) the function of the consultation in section 21 of the Act, the Administrative Court is authorized to accept, examine and decide to settlement misappropriation authority by government; 2) judicial functions in section 53 and 87 of the Act, the Administrative Court has the authority to receive, examine and decide upon applications for receipt of applications to obtain decisions and/or actions of government or authority.